Beyond anthropomorphism: Unraveling the true priorities of chatbot usage in SMEs - MAKANY, Tamas (Institutional Knowledge at Singapore Management University, 2023)
This study examined business communication practices with chatbots among various Small and Medium Enterprise (SME) stakeholders in Singapore, including business owners/employees, customers, and developers. Through qualitative interviews and chatbot transcript analysis, we investigated two research questions: (1) How do the expectations of SME stakeholders compare to the conversational design of SME chatbots? and (2) What are the business reasons for SMEs to add human-like features to their chatbots? Our findings revealed that functionality is more crucial than anthropomorphic characteristics, such as personality and name. Stakeholders preferred chatbots that explicitly identified themselves as machines to set appropriate expectations. Customers prioritized efficiency, favoring fixed responses over free text input. Future research should consider the evolving expectations of consumers, business owners, and developers as chatbot technology advances and becomes more widely adopted.